P2-S8.10 Measuring social media efforts: beyond click throughs. (10th July 2011) - Kachur, R; Richman, L; Hable, M; Verma, R; Friedman, A; Kapsimalis, C; McFarlane, M; Patel, A
Abstract : Background: With the rapid expansion of social media, public health organizations have been quick to adopt these new channels to reach target populations. Typically, however, these efforts are accompanied by minimal evaluation and results are not routinely used to inform and improve programs. The GYT: Get Yourself Tested campaign, a national, US campaign to increase STD testing and decrease stigma is a case study that illustrates the challenges and the importance of evaluating social media. Methods: Between 1 April 2009 and 30 September 2010, metrics data for the GYT: Get Yourself Tested campaign were collected and evaluated from such social media venues as Facebook, Twitter, the GYTnow SMS code, and the GYTnow campaign website. Facebook and Twitter usage were indicators of user engagement with the campaign, and behavioural intentions were measured through use of a STD testing center locator from the GYT website and use of the GYT Short Message Service (SMS) code. A mobile phone user can send a zip code to the SMS service to receive information about local testing centers. Results: Evaluation of the GYT social media efforts allowed campaign organisers to measure campaign reach and engagement, customer sentiment, and intentions to get tested for STDs. The campaign reached over one million people in five national, social media venues. The Facebook site recruited 4177 fans, and the Twitter account had 1719 followers. The testing center locator was used by 64 000 people; 51, 000 people used the SMS code to locate services. Qualitative data provided additional information about campaign sentiment as well as barriers to participation in the campaign. Analysis of the various metrics also uncovered unexpected issues such as a significant dip in participation in April as a result of a lack of participation by one of the major phone carriers. Conclusions: Evaluating social media metrics can provide an in-depth understanding of how well target audiences are being reached, how information and messages resonate with them and how efforts can be improved or changed. Findings from this analysis help illustrate the need to adequately evaluate social media efforts, guide future social media evaluations, and understand audience behaviours when engaging in social media activities. Additional web analytic studies are needed to better understand the impact of social media use for STD prevention.